MARTENSITE ORDERING AND STABILIZATION IN COPPER-BASED SHAPE-MEMORY ALLOYS - ADIGUZEL, O (Pergamon-Elsevier Science Ltd, 1995)
Stabilization behavior of the martensite in shape memory CuZnAl and CuAlMn alloys has been studied by x-ray measurements and electron microscopy. In these alloys influenced by both quenching and post-quench heat treatments, the degree of stabilization depends on quenching conditions. The stabilization process is mainly due to structural change and atomic arrangement in the martensitic lattice inherited from the parent phase. From x-ray results, it is suggested that stabilization and loss of memory are directly related to disordering in a martensitic state. In the present study, it was concluded that the spacing differences (Delta d) between some selected pairs of diffraction planes of type (h(1)k(1)1) and (h(2)k(2)1) satisfying the relation (h(1)(2) - h(2)(2))/3 = (k(2)(2) - k(1)(2))/n, with n = 1 for 9R and n = 4 for 18R martensites reflect the degree of ordering in martensite, in addition to the lattice distortion parameters defined as phi = \sin(2) theta(202) - sin(2) theta(122)\ and phi(1) = \sin(2) theta(320) - sin(2) theta(040)\.
Keywords: COPPER; ZINC; ALUMINUM; MANGANESE; SHAPE MEMORY ALLOYS